Profil Sikap Ilmiah Peserta Didik Melalui Kegiatan Praktikum Menggunakan E-LKPD Berbasis Bahan Kimia di Rumah - Febri Saputri; Eli Rohaeti; Antuni Wiyarsi; Jaslin Ikhsan (Jurnal Penelitian Pendidikan IPA, 2022)
Students’ competencies in the 21st century can be achieved if the students have various skills and scientific attitudes. Scientific Attitude will affect students' minds or memories and actions that require in making decisions and problem-solving in the future. So, the aim of this study was to describe the profile of students' scientific attitudes through Practicum Activities Using Student E-Worksheet Based Chemicals at Home. This research used a descriptive quantitative method. The research was conducted in Budi Mulia Dua senior high school, Yogyakarta, Indonesia, at the last of the first semester of the academic year 2021/2022. The observation involved 15 of tenth-grade students as the participant. The data was collected using an observation sheet which was developed based on students' scientific attitude aspects. The instrument has been validated by expert learning lecturers so that it is feasible to use. The data obtained from the students were analyzed descriptively and quantitatively. The results of students’ scientific attitudes were in the good category ie. 75.8%. Therefore, teachers need to innovate the learning process in order to improve students' scientific attitudes